Predicting tendency to abuse drugs based early maladaptive schemas and perfectionism in students - afsaneh mansourijalilian; kamran yazdanbakhsh (Drug Control Headquarters, Research and Education Office, 2015)
Introduction: The aim of this study is to predict trends to drug abuse based on the early maladaptive schemas and perfectionism among college students. The participants of this study were Razi university students. Method: the study design is descriptive- correlation that 288 people, female (n= 137) and male‌ (n=137) were selected by multistage cluster sampling, and they filled out tendency to drug abuse (Wed, et.al.1992), young's early maladaptive schemas (short from ,2005) and positive and negative perfectionism questionnaires(Terry-short et al 1995). For analyzing the obtained data, stepwise regression method was used. Results: The results of this study showed that the schema, mistrust/Abuse, dependence/Incompetence, subjugation and restraint/ discipline insufficient predicting tendency to drug abuse. Conclusion: the results indicated that the negative perfectionism predicting tendency to drug abuse, however, the positive perfectionism cannot predict tendency to drug abuse